CD3+ B-1a Cells as a Mediator of Disease Progression in Autoimmune-Prone Mice. (23rd December 2018) - Yamamoto, Wakako; Toyoda, Hidemi; Xu, Dong-qing; Hanaki, Ryo; Morimoto, Mari; Nakato, Daisuke; Ito, Takahiro; Iwamoto, Shotaro; Bonno, Motoki; Tanaka, Shigeki; Hirayama, Masahiro
Abstract : B-1a cells are distinguishable from conventional B cells, which are designated B-2 cells, on the basis of their developmental origin, surface marker expression, and functions. In addition to the unique expression of the CD5 antigen, B-1a cells are characterized by the expression level of CD23. Although B-1a cells are considered to be independent of T cells and produce natural autoantibodies that induce the clinical manifestations of autoimmune diseases, there is much debate on the role of B-1a cells in the development of autoimmune diseases. We examined the involvement of B-1a cells in autoimmune-prone mice with the lpr gene. MRL/ lpr and B6/ lpr mice exhibited lupus and lymphoproliferative syndromes because of the massive accumulation of CD3+CD4-CD8-B220+ T cells. Interestingly, the B220+CD23-CD5+ (B-1a) cell population in the peripheral blood and peritoneal cavity increased with age and disease progression. Ninety percent of B-1a cells were CD3 positive (CD3+ B-1a cells) and did not produce tumor necrosis factor alpha, interferon gamma, or interleukin-10. To test the possible involvement of CD3+ B-1a cells in autoimmune disease, we tried to eliminate the peripheral cells by hypotonic shock through repeated intraperitoneal injections of distilled water. The fraction of peritoneal CD3+ B-1a cells decreased, and symptoms of the autoimmune disease were much milder in the distilled water-treated MRL/ lpr mice. These results suggest that CD3+ B-1a cells could be mediators of disease progression in autoimmune-prone mice.